"AN INNOVATIVE APPROACH IN MUSIC CIRCLES: THE IMPORTANCE AND IMPLEMENTATION EXPERIENCE OF CROSS-PLATFORM TECHNOLOGIES" (Scientific journal of the Fergana State University, 2026)
This article explores the importance of the cross-platform approach in music education. Based on the experimental results, this approach has been identified as a crucial tool for enhancing students' creativity and organizing the educational process in an interactive and effective manner. Developing specialized programs for national instruments and improving teachers' technological literacy are recommended as key strategies.